2019
DOI: 10.1002/aur.2233
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the factor structure of the child behavior checklist dysregulation profile in children and adolescents with autism spectrum disorder

Abstract: Dysregulation has been identified as an important risk factor for the development of psychiatric disorders in individuals with autism spectrum disorder (ASD). Therefore, it is necessary to empirically characterize dysregulation and identify psychometrically sound and readily available assessment methods in the ASD population. We sought to evaluate the factor structure of the Child Behavior Checklist‐Dysregulation Profile (CBCL‐DP), an established dysregulation measure in neurotypical children that is derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
(45 reference statements)
1
5
0
1
Order By: Relevance
“…This might be particularly suitable when studying youth dysregulation since behavioral–genetic studies and theoretically based models showed that, when described by a DP, dysregulation is distinct from its specific components [ 33 36 ], and so it should be conceptualized as a transdiagnostic syndrome that exists next to specific problems (i.e., Hyperactivity–Inattention, Emotional Symptoms, Conduct Problems) [ 37 ]. A bifactor model would better capture this conceptualization, as also suggested by our results and several studies exploring the DP with different measures (e.g., SDQ, CBCL, Youth Self Report, Teacher Report Form) and samples [ 9 , 36 , 38 , 39 ]. Finally, the examination of the factor loadings revealed that all the items significantly loaded into the general factor DP and their specific factors (see Table 4 ), with most of the factor loadings of the general factor above 0.40, supporting the bifactor nature of the SDQ-DP 15-item teacher-report.…”
Section: Discussionsupporting
confidence: 67%
“…This might be particularly suitable when studying youth dysregulation since behavioral–genetic studies and theoretically based models showed that, when described by a DP, dysregulation is distinct from its specific components [ 33 36 ], and so it should be conceptualized as a transdiagnostic syndrome that exists next to specific problems (i.e., Hyperactivity–Inattention, Emotional Symptoms, Conduct Problems) [ 37 ]. A bifactor model would better capture this conceptualization, as also suggested by our results and several studies exploring the DP with different measures (e.g., SDQ, CBCL, Youth Self Report, Teacher Report Form) and samples [ 9 , 36 , 38 , 39 ]. Finally, the examination of the factor loadings revealed that all the items significantly loaded into the general factor DP and their specific factors (see Table 4 ), with most of the factor loadings of the general factor above 0.40, supporting the bifactor nature of the SDQ-DP 15-item teacher-report.…”
Section: Discussionsupporting
confidence: 67%
“…The CBCL-DP is a profile derived from three different subscales that covers aspects of a dysregulation construct: an affective component (Anxiety and Depressive problems), a behavioral component (Aggressive problems), and a cognitive component (Attention problems; Keefer et al, 2020). Recent evidence supports the association of the CBCL-BP/DP (Biederman et al, 1995, Mick et al, 2003) with a diagnosis of pediatric bipolar disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we performed the CFA to test the fit of the five-factor PERMA model specified by Bulter and Kern 27 as well as a bifactor model, which tests whether PERMA can be represented as a single overall factor, rather than with five discrete factors. 32 , 33 We evaluated the fit of each model using the root mean square error of approximation (RMSEA) and standardized root mean residual (SRMR). An RMSEA of 0.08 or below (and a lower 90% confidence interval bound <0.05) and an SRMR of 0.08 or lower indicate acceptable model fit, while values less than 0.06 indicate excellent fit.…”
Section: Methodsmentioning
confidence: 99%